2023
DOI: 10.1038/s41427-023-00465-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress with one-dimensional metal halide perovskites: from rational synthesis to optoelectronic applications

Abstract: Metal halide perovskites can be readily synthesized, they exhibit tunable physical properties and excellent performance, and they are heavily studied optoelectronic materials. Compared to the typical three-dimensional perovskites, morphological-level one-dimensional (1D) nanostructures enable charge transport and photon propagation with low exciton binding energies and long charge-carrier diffusion lengths, while molecular-level 1D nanostructures exhibit good compositional and structural flexibilities, highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 156 publications
0
9
0
Order By: Relevance
“…All of these results indicated that these inorganic materials are promising alternatives for optoelectronic applications too. 172,173…”
Section: Applications and Perspectivesmentioning
confidence: 99%
“…All of these results indicated that these inorganic materials are promising alternatives for optoelectronic applications too. 172,173…”
Section: Applications and Perspectivesmentioning
confidence: 99%
“…The 1D perovskite nanostructures are typically synthesized using wet-chemical methods, such as organic ligand-mediated growth, phase transition control, oriented attachment, and anion exchange. [91][92][93][94][95][96]97] Substrate-assisted methods, such as polymer matrix-assisted growth, dissolution-recrystallization strategy, and vapor-phase deposition, have also been used to synthesize 1D perovskite nanostructure. [98][99][100] In addition to singlephase 1D perovskite nanorods (NRs), heterojunctions of different phases have also been synthesized.…”
Section: Phase Transition In 1d Perovskite Nanostructurementioning
confidence: 99%
“…Besides, the dimensionality of HOMHs is variable, which exerts a significant impact on their luminescent properties. Shrinking the dimensionality of HOMHs from three-dimensional (3D) to low-dimensional (2D, 1D, 28 0D) can endow them with unique properties such as large exciton binding energy, multiple quantum wells and confinement effects, 29 controllable charge-carrier mobility, and efficient photoluminescence intensity. 30–32 Low-dimensional metal halides have thus been witnessed to exhibit high photoluminescence quantum yield (PLQY) and broad emission range 33 on account of the formation of self-trapped excitons (STEs).…”
Section: Introductionmentioning
confidence: 99%